The Fourth Person of the Trinity. The Phantasmatic Flesh of Christ and the Extra-Ontological Dehiscence - Prósperi, Germán Osvaldo (Revista de Filosofía, 2020)
The aim of this paper is to analyse, from a logical and ontological perspective, the conceptof a fourth person in the Trinity, as it is presented by John of Damascus in De fide orthodoxa and Deimaginibus. We argue that this fourth person challenges the logic of the trinitarian theology. Since thefourth person is irreducible to the divine or the human, or to the matter and the spirit, its nature fallsbeyond the ontology. Consequently, an extra-grammar fourth person, one beyond syntax, is requiredto verbalise it.
Keywords: Fourth person of the Trinity; Christ; flesh; hypostasis; phantasmatic; John Damascene